Does Circadian Disruption Play a Role in the Metabolic–Hormonal Link to Delayed Lactogenesis II? - Fu, Manjie; Zhang, Lingsong; Ahmed, Azza; Plaut, Karen; Haas, David M.; Szucs, Kinga; Casey, Theresa M. (Frontiers in Nutrition, 2015)
Breastfeeding improves maternal and child health. The American Academy of Pediatrics recommends exclusive breastfeeding for six months, with continued breastfeeding for at least one year. However, in the US, only 18.8% of infants are exclusively breastfed until six months of age. For mothers who initiate breastfeeding, the early postpartum period sets the stage for sustained breastfeeding. Mothers who experience breastfeeding problems in the early postpartum period are more likely to discontinue breastfeeding within two weeks. A major risk factor for shorter breastfeeding duration is delayed lactogenesis II (i.e. onset of milk "coming in" more than 72 h postpartum). Recent studies report a metabolic-hormonal link to delayed lactogenesis II. This is not surprising because around the time of birth the mother’s entire metabolism changes to direct nutrients to mammary glands. Circadian and metabolic systems are closely linked, and our rodent studies suggest circadian clocks coordinate hormonal and metabolic changes to support lactation. Molecular and environmental disruption of the circadian system decreases a dam’s ability to initiate lactation and negatively impacts milk production. Circadian and metabolic systems evolved to be functional and adaptive when lifestyles and environmental exposures were quite different from modern times. We now have artificial lights, longer work days, and increases in shift work. Disruption in the circadian system due to shift work, jet lag, sleep disorders and other modern life style choices are associated with metabolic disorders, obesity, and impaired reproduction. We hypothesize delayed lactogenesis II is related to disruption of the mother’s circadian system. Here we review literature that supports this hypothesis, and describe interventions that may help to increase breastfeeding success.